2007
DOI: 10.1021/jf0624594
|View full text |Cite
|
Sign up to set email alerts
|

6-Shogaol (Alkanone from Ginger) Induces Apoptotic Cell Death of Human Hepatoma p53 Mutant Mahlavu Subline via an Oxidative Stress-Mediated Caspase-Dependent Mechanism

Abstract: Mahlavu cells, poorly differentiated and p53 mutants of a human hepatoma subline, are known to be highly refractory to a number of chemotherapeutic agents and radiotherapy due to their high expressions of multidrug resistance gene-1 (MDR-1) and Bcl-2 proteins. Thus, it is desirable to search for an alternative strategy for effective eradication of this type of cancer cells. We present evidence here for the first time that 6-shogaol (6-SG), an alkanone isolated from the rhizomes of ginger, can effectively induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 24 publications
4
73
1
Order By: Relevance
“…It has been shown that the collapse of DC and the redistribution of cytochrome care early steps in the apoptotic cascade. A rapid collapse of mitochondrial transmembrane electrical potential is always found in some anticancer compounds-induced apoptosis in cancer cells (Chen et al 2007). Our data show that quercetin could induce a rapid collapse of DCm, which means that quercetin-induced apoptosis is related to the collapase of DCm.…”
Section: Discussionsupporting
confidence: 52%
“…It has been shown that the collapse of DC and the redistribution of cytochrome care early steps in the apoptotic cascade. A rapid collapse of mitochondrial transmembrane electrical potential is always found in some anticancer compounds-induced apoptosis in cancer cells (Chen et al 2007). Our data show that quercetin could induce a rapid collapse of DCm, which means that quercetin-induced apoptosis is related to the collapase of DCm.…”
Section: Discussionsupporting
confidence: 52%
“…Many studies have shown that the collapse of the mitochondrial membrane potential and the redistribution of cytochrome c are early steps in the apoptotic cascade (Kluck et al, 1997;Wang, 2001). A rapid collapse of ΔΨ m is always found in some anticancer compounds-induced apoptosis in cancer cells (Chen et al, 2007). In this study, we investigated the effects of curcumin on the ΔΨ m with fluorescent dye JC-1.…”
Section: Discussionmentioning
confidence: 98%
“…O 2 -can also rapidly react with another free radical, nitric oxide (NO), yielding more toxic ROS such as peroxynitrite (OONO -) through the catalytic action of eNOS present in this organelle. 58,59 The depletion of mGSH can then be proceeded via the interaction of NO and GSH: …”
Section: Discussionmentioning
confidence: 99%